Wasiat Wajibah Kepada Anak Angkat: Analisis Terhadap Keputusan Dan Metode Penghakiman dalam Kes No 459/Pdt.G/2013/Pta Sby: Wajibah Will toward Adopted Child: An Analysis of Decision and Method of Judgment in the Case Number 459/Pdt.G/2013/PTA Sby - Muhammad Daud, Zakiul Fuady; Azahari, Raihanah Hj (Jurnal Fiqh, 2018)
Adoption is a common practice to continue the heredity. The purpose of this study is to identify and analyze the decision and methods of judgment used by the judge in awarding the wajibah will to the adopted child. This descriptive qualitative study uses an interview and documentation as collecting data method. The data analysis uses 4 stages recommended by Miles and Huberman. The findings of the study show that judges grant wajibah to adopt child and use the grammatical interpretation method toward the provisions contained in compilation of Islamic law (KHI) section 209. If the decision and method of judgment are analyzed in the perspective of shariah, they are not appropriate because the status of the adopted child is not equal to the biological child who has different positions in Islamic inheritance law. While the methods used by the judges can indeed be used but it should refer to the provisions in Islamic inheritance law directly.